Development and testing of a standardized training manual : diet and the nutritional management of diabetes mellitus : a comprehensive guide for health practitioners - Rausch, Ursula (Stellenbosch : Stellenbosch University, 2014)
Thesis (MNutr)--Stellenbosch University, 2014.